Oral communication skill in English: a comparative study on final semester Bachelor of Accountancy and Bachelor of Business Administration students of UiTM Machang, Kelantan / Wan Muzlaina Wan Mustafa, Razana Juhaida Johari and Norazida Mohamed - Wan Mustafa, Wan Muzlaina; Johari, Razana Juhaida; Mohamed, Norazida (2005)
This is an assessment of oral communication skills in English of final semester students of Bachelor of Accountancy (BAcc) and Bachelor of Business Administration ( BBA) of Universiti Teknologi MARA (UiTM) Kelantan Campus. This study is solely through the use of Assessment Form (evaluation form). This assessment form was distributed to English lecturers and two different group of students (BAcc and BBA-Finance) as an assessors. The Assessment Form used in this survey was that the one used by the English lecturers at the language center of UiTM in assessing the English Oral Communication skills of students' presentation in all facilities in UiTM. The findings of the study indicate that, there is a significant difference between lecturers' assessment and students' assessment on the level of English oral communication skills of BAcc and SBA-Finance students. The result also revealed that, the mean mark of the lecturers are much lower compared to the students' mean mark in both BAcc and BBA-Finance. However, based on the mean mark, range of marks and standard deviation, it shows the assessments of BAcc students are more closer to the lecturers' assessment. It can be concluded that, BAcc and BBAFinance students are not in a position (but BAcc is better) in making a reasoned assessment independent of their own level of English oral communication skills and to assess their own performance in preparing the oral communication skiils in the future.